2021
DOI: 10.1073/pnas.2100342118
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine FAM3B/PANDER is an FGFR ligand that promotes posterior development in Xenopus

Abstract: Fibroblast growth factor (FGF)/extracellular signal-regulated kinase (ERK) signaling plays a crucial role in anterior–posterior (A–P) axial patterning of vertebrate embryos by promoting posterior development. In our screens for novel developmental regulators in Xenopus embryos, we identified Fam3b as a secreted factor regulated in ectodermal explants. Family with sequence similarity 3 member B (FAM3B)/PANDER (pancreatic-derived factor) is a cytokine involved in glucose metabolism, type 2 diabetes, and cancer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Overexpression of Xenopus fam3b mRNA or injection of recombinant FAM3B protein into the blastocoel cavity inhibited cephalic structures and induced ectopic tail‐like structures, indicating FGF‐like activity. In vitro, FAM3B protein bound to FGFR extracellular domain‐Fc fusion proteins for FGFRs 1–4 and activated the downstream ERK signaling in an FGFR‐dependent manner (F. Zhang, Zhu, et al, 2021).…”
Section: Regulation Of Fgfr Signal Transduction By Extracellular and ...mentioning
confidence: 99%
“…Overexpression of Xenopus fam3b mRNA or injection of recombinant FAM3B protein into the blastocoel cavity inhibited cephalic structures and induced ectopic tail‐like structures, indicating FGF‐like activity. In vitro, FAM3B protein bound to FGFR extracellular domain‐Fc fusion proteins for FGFRs 1–4 and activated the downstream ERK signaling in an FGFR‐dependent manner (F. Zhang, Zhu, et al, 2021).…”
Section: Regulation Of Fgfr Signal Transduction By Extracellular and ...mentioning
confidence: 99%
“…Notably, in addition to the typical FGF/FGFR pathways mentioned above, there are also some atypical examples. For instance, in Xenopus embryos, FGFR is activated by family with sequence similarity 3 member B to activate downstream ERK signaling and promote posterior development, forming an anterior–posterior axial pattern 55 . Furthermore, activation of ERK induces remodeling of cytoskeletal proteins, including F‐actin, embryonic calmodulin C‐cadherin, and the tight junction protein zonula occluden‐1, which is required for enhanced cellular junctions and tissue sclerosis during early embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…6 A). We focused on the DEGs that are also highly expressed: LHX1 (associated in Müllerian agenesis; Huang et al, 2014 ), HOXD8 (homeobox gene that is highly expressed during the development of the chicken MD; Roly et al, 2020 ), FAM3B (a recently identified FGFR ligand implicated in posterior development; Zhang et al, 2021 ), NDN , androgen receptor ( AR ) and GATA5 (expressed during the MD development and associated with abnormalities of the genitourinary tract of female mice; Roly et al, 2020 ; Molkentin et al, 2000 ). Quantitative PCR assays clearly validated the RNA-sequencing results ( Fig.…”
Section: Resultsmentioning
confidence: 99%